Sex difference in initial thermoregulatory response to dehydrated exercise in the heat. Issue 14 (20th July 2021) - Giersch, Gabrielle E. W.; Morrissey, Margaret C.; Butler, Cody R.; Colburn, Abigail T.; Demarais, Zachariah S.; Kavouras, Stavros A.; Jay, Ollie; Charkoudian, Nisha; Casa, Douglas J.
Abstract: Although it is well established that dehydration has a negative impact on thermoregulation during exercise in the heat, it is unclear whether this effect of dehydration is different between men and women, or across the phases of the menstrual cycle (MC). Twelve men and seven women (men: 20 ± 2 years, 70.13 ± 10.5 kg, 173.4 ± 6.0 cm, 54.2 ± 8.6 ml kg −1  min −1 ; women: 20 ± 2 years, 57.21 ± 7.58 kg, 161 ± 5 cm, 40.39 ± 3.26 ml kg −1  min −1 ) completed trials either euhydrated (urine specific gravity, USG ≤ 1.020, Euhy) or dehydrated (USG > 1.020, Dehy). Trial order was randomized and counterbalanced; men completed two trials (MEuhy and MDehy) and women completed four over two MC phases (late follicular: days 10–13, FDehy, FEuhy; midluteal: days 18–22, LDehy, LEuhy). Each trial consisted of 1.5 h, split into two 30 min blocks of exercise (B1 and B2, 15 min at 11 W/kg & 15 min at 7 W/kg) separated by 15 min rest in between and after. Rectal temperature ( T re ) was measured continuously and estimated sweat loss was calculated from the body mass measured before and after each block of exercise. When dehydrated, the rate of rise in T re was greater in women in the first block of exercise compared to men, independently of the MC phase (MDehy: 0.03 ± 0.03°C/min, FDehy: 0.06 ± 0.02, LDehy: 0.06 ± 0.02, p  = 0.03). Estimated sweat loss was lower in all groups in B1 compared to B2 when dehydrated ( p  < 0.05), with no difference between sexes for either hydration condition. These data suggest that women may be more sensitive to the negative thermoregulatory effects of dehydration during the early stages of exercise in the heat. Abstract : This study investigated possible sex and menstrual cycle differences to the thermoregulatory response to dehydrated exercise in the heat. We observed a possible augmented core temperature response in women, irrespective of the menstrual cycle phase. Understanding these sex differences will aide in the development of recommendations for all physically active individuals.